SISTEM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA PERGURUAN TINGGI UMUM: Studi Kasus di Universitas Nusantara PGRI Kediri - Rifqi Amin (Sekolah TinggiAgama Islam Negeri (STAIN) Kediri, 2013)
The study describes the implementation of Islamic teaching at UNP Kediri. This is qualitative in nature. The findings are as follows. Firstly, the teaching materials of Islamic teaching at UNP consist of main topics and some others developed to meet the characteristics of the students. Secondly, the specific competences required are the unity of God, character, and problem solving. Thirdly, the strategies used by the teachers are the flexibility of classroom rules, providing models, and contextual teaching. And fourthly, the evaluation is mainly affective evaluation.